2018
DOI: 10.5005/jp-journals-10024-2396
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency of Three Irrigating Solutions after Surgical Removal of Impacted Mandibular Third Molars: A Cross-sectional Study

Abstract: Aim: The present study was conducted to assess the effect of irrigation with three different irrigants, namely normal saline, chlorhexidine, and povidone iodine on pain, alveolar osteitis, swelling, trismus, infection, and food impaction during surgical removal of impacted mandibular third molar. Materials and methods: Forty-eight patients, including 26 males and 22 females, fulfilling criteria for inclusion in this study were divided into three groups: group I where irrigant used was normal saline, group II a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…A comparative study 31 assessed the use of saline vs. 0.12% chlorhexidine rinse and found no significant difference in AO incidence between the two interventions. Jadhao 32 compared saline, chlorhexidine and povodine iodine irrigation and noted a significant reduction in AO incidence with chlorhexidine rinsing.…”
Section: Resultsmentioning
confidence: 99%
“…A comparative study 31 assessed the use of saline vs. 0.12% chlorhexidine rinse and found no significant difference in AO incidence between the two interventions. Jadhao 32 compared saline, chlorhexidine and povodine iodine irrigation and noted a significant reduction in AO incidence with chlorhexidine rinsing.…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis studying the contribution of PRF (Platelet-rich Fibrin) in the sockets confirmed significant improvement regarding pain, edema and onset of osteitis [ 24 ]. A study demonstrated greater efficacy of irrigating the site with chlorhexidine versus saline solution and iodinated povidone on reducing postoperative pain, edema and trismus [ 25 ]. Reyes-Gilabert et al [ 26 ] identified a statistically significant association between pre- and postoperative anxiety and also between postoperative anxiety and pain in oral surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative sequelae, such as pain, trismus, swelling, and chewing problems, commonly arise after tissue injury. Numerous researchers have studied the effects of various preoperative, intraoperative, and postoperative intervention strategies to avoid or decrease the degree of discomfort due to inflammation induced by tissue injury during the surgical removal of mandibular third molars [ 26 34 ]. Here, we demonstrated that the application of an iodine-containing tampon reduced the amount of perceived postoperative discomfort, and thus improved the OHRQoL.…”
Section: Discussionmentioning
confidence: 99%